Using superparamagnetic iron oxide nanoparticles to enhance bioavailability of quercetin in the intact rat brain - Rezvan Enteshari Najafabadi; Nasrin Kazemipour; Abolghasem Esmaeili; Siamak Beheshti; Saeed Nazifi (BMC, 2018)
Abstract Background Quercetin (QT) as a bioactive flavonoid has a potential therapeutic activity for numerous neuronal injuries and neurodegenerative diseases. However, the low absorption rate of QT, especially through the blood-brain barrier, restricts its bioactivity in the body. The current research took the advantage of superparamagnetic iron oxide nanoparticles (SPIONs) to enhance the bioavailability of quercetin. Methods Quercetin conjugated with SPIONs was prepared by means of nanoprecipitation method and was characterized by X-ray diffractometer, scanning electron microscope, and Fourier transformed infrared spectrometer analyses. Wistar male rats were orally fed by gavage with QT and QT-SPION at 50 and 100 mg/kg daily doses for 7 days. Using high-performance liquid chromatography (HPLC) method, biodistribution of QT was evaluated in plasma and brain tissue. Results The outcomes of this research revealed a higher concentration in the plasma and brain of the rats fed with QT-SPION in comparison to free QT. Conclusion The results of this study confirm that SPION as a targeted drug delivery system enhances the bioavailability of quercetin in the brain about ten folds higher than free quercetin and could be used for the treatment of neurodegenerative disorders.